Information technologies, geoinformation systems and cartographic support in the system of professional training of tourism experts and geographers - Prykhodko, Z.; Sych, V.; Shashero, A.; Molodetskiy, A.; Nefedova, N. (Journal of Education, Health and Sport, 2024)
The article is devoted to the problems of using information technologies, Geographic Information Systems and cartographic materials in the tourism sector, both in the educational process and directly in the work of tourist enterprises. Emphasis is placed on specialized software products for solving the management problems of tourist enterprises. The article describes the functional features of maps, GIS products, and Internet resources used for cartographic support of tourist and recreational activities.